Early career teachers navigating the landscape of SACRE in England - Mogra, Imran (Journal of beliefs and values, 2026)
As a contribution to continuing debates about RE in England, this study explores current perspectives on the determination of the syllabus for RE of trainee teachers in a university in the West Midlands. They were selected because trainees are rarely studied in academic research about locally agreed syllabi. A survey gathered 149 responses from PGCE and Year 3 undergraduate students and 52 questionnaires from Year 1. The central concern is to explore the structural matters concerning the Standing Advisory Council on RE. The findings highlight the diverse perspectives regarding the role of the Church and of religion in society, and the control of RE, nationally and locally. This diversity is echoed in the distinct rationale for RE legislation, policy and praxis and is reflected among these trainees. The findings underscore the importance of addressing these varied views in developing RE policies and curricula to ensure they reflect the democratic values and needs of future educators. The emphasis on democratic processes in syllabus development could serve as a model for other countries considering their RE frameworks. This research reveals a call for a statutory curriculum, for SACREs to continue and for agreed syllabuses to be products of a democratic process.